The international labor scene. Industrial relations research association. Proceeding of the spring meeting. Philadelphia, Penn., May 8-9. 1962. [With contribs. of F.A. Breier, Koji Taira, Arthur M. Ross a.o.]
Repr.: Labor Law journal, 1962, July, p. 477-595.